Implementation of Probing – Prompting Model on Students' Critical Thinking Skills in Learning Civics Education Through Quizizz - Diah Citra Raesi; Endang Danial AR; Syaifullah Syaifullah (Jurnal Civicus, 2020)
Based on the background on observations in the VII-G class during the study of PKn. It was found that students had a motivational learning and low critical thinking ability. The purpose of this research is to improve students' critical thinking in class VII-G SMP Negeri 40 Bandung with probing learning Model –prompting. This research uses qualitative and quantitative approaches to the method of class action research (PTK). This research was conducted in SMPN 40 Bandung with research participants of teachers and students of class VII-G SMPN 40 Bandung. Data collection In this research is done through observation, interviews, documentation study, literature study, field records with processing/data analysis techniques using data-triangulation technique i.e. data reduction, data presentation, conclusion/verification (conclusion). The results obtained from research with model probing-following prompting during the three meetings/cycles showed an increase in students' critical thinking ability, cycles of 1 24.2% "less", cycle II 34.9% "less" and cycle III 60.8% "insufficient". Probing-prompting models are not only for increasing student critical  thinking  but helping students to expand all  questions,  describing new knowledge, being able to help motivate learning better.